Imaging c-Met expression using 18F-labeled binding peptide in human cancer xenografts. - Weihua Li; Hongqun Zheng; Jiankai Xu; Shaodong Cao; Xiuan Xu; Peng Xiao; Peng Xiao (PLoS ONE)
Objectives c-Met is a receptor tyrosine kinase shown inappropriate expression and actively involved in progression and metastasis in most types of human cancer. Development of c-Met-targeted imaging and therapeutic agents would be extremely useful. Previous studies reported that c-Met-binding peptide (Met-pep1, YLFSVHWPPLKA) specifically targets c-Met receptor. Here, we evaluated 18F-labeled Met-pep1 for PET imaging of c-Met positive tumor in human head and neck squamous cell carcinoma (HNSCC) xenografted mice. Methods c-Met-binding peptide, Met-pep1, was synthesized and labeled with 4-nitrophenyl [18F]-2-fluoropropionate ([18F]-NPFP) ([18F]FP-Met-pep1). The cell uptake, internalization and efflux of [18F]FP-Met-pep1 were assessed in UM-SCC-22B cells. In vivo pharmacokinetics, blocking and biodistribution of the radiotracers were investigated in tumor-bearing nude mice by microPET imaging. Results The radiolabeling yield for [18F]FP-Met-pep1 was over 55% with 97% purity. [18F]FP-Met-pep1 showed high tumor uptake in UM-SCC-22B tumor-bearing mice with clear visualization. The specificity of the imaging tracer was confirmed by significantly decreased tumor uptake after co-administration of unlabeled Met-pep1 peptides. Prominent uptake and rapid excretion of [18F]FP-Met-pep1 was also observed in the kidney, suggesting this tracer is mainly excreted through the renal-urinary routes. Ex vivo biodistribution showed similar results that were consistent with microPET imaging data. Conclusions These results suggest that 18F-labeled c-Met peptide may potentially be used for imaging c-Met positive HNSCC cancer in vivo and for c-Met-targeted cancer therapy.